Technology as a Means of Human Liberation in the Perspective of Herbert Marcuse - Kwirinus, Dismas; Pandor, Pius; Yuniarto, Petrus (International Journal of Indonesian Philosophy & Theology, 2024)
The focus of this research examines technology as a means of human liberation from the perspective of Herbert Marcuse. This research aims to investigate and look at new technology, namely technology that leads to the goal of complete human development. The development of human dignity is the goal of technology because technology is a means of human liberation to achieve its fullness. Technology is not a means of domination in various areas of life. Researchers used descriptive qualitative methods and critical reading of texts. Based on critical reading of the text, the researcher analyzes and combines materials related to Herbert Marcuse's views on One Dimensional Man. The findings in this research are that Marcuse does not reject technology because of the close relationship between technology and human development. Although it cannot be denied that industrial society, with its technology, oppresses humans, it does not invite humans to return to the pre-industrial or pre-technical era. Instead, it continues to turn to the liberating capabilities of technology and industrialization.